Factors Influencing the Consumer’s Decision Using Financial Technology: Case Study in Jakarta - Renny Risqiani; Ari Mulianta Ginting (Jurnal Ekonomi & Kebijakan Publik, 2022)
Economic evolution started with the first wave of the industrial revolution. Economic evolution brought about changes in the economy. One of these effects is the advancement of technology, which has increased the use of Financial Technology (Fintech) in Indonesia. Fintech usage has risen in Indonesia, particularly in Jakarta. The study’s goal is to look at the elements that influence people’s decision to keep using fintech services. The study used non-probability sampling methods to obtain data from fintech users in Jakarta aged 17 to 35 years old over the research period of March to May 2020. The data was analyzed by using Structural Equation Model (SEM) with the AMOS software program. This study found that competitive pressures in technology services and the ease of digital technology offer consumers a wide range of options. Customers easily switch to other technology services at a reasonably affordable price. The study also found that variable consumer perceptions of benefits and trust variables in fintech services influence consumer attitudes. However, these two variables have no direct effect on the desire to continue using fintech services. Variable risk perception does not affect the attitude and desire of consumers to continue using fintech services. Variable attitudes affect the desire to continue using fintech services. The study results showed that increasing the penetration of fintech and continue consumers to continue to use fintech. It is necessary to improve risk perception to fintech used by consumers.Keywords: fintech, benefit and risk perception, Structural Equation Model AbstrakPerkembangan evolusi perekonomian dimulai dari gelombang pertama hingga masuk revolusi industri membawa perubahan terhadap perekonomian. Salah satu dampak tersebut adalah semakin berkembangnya teknologi. Perkembangan teknologi membawa dampak terhadap peningkatan Financial Technology (Fintech) di Indonesia. Penggunaan fintech di Indonesia mengalami peningkatan khususnya penggunaan fintech di Jakarta. Penelitian ini bertujuan untuk menganalisis faktor-faktor yang memengaruhi niat untuk terus memanfaatkan layanan fintech. Studi ini mengumpulkan data dari pengguna fintech di Jakarta yang berusia 17 hingga 35 tahun menggunakan metode non-probability sampling dengan periode penelitian dari bulan Maret – Mei tahun 2020. Analisis data menggunakan Structural Equation Model (SEM) dengan program software AMOS. Studi ini menemukan bahwa tekanan persaingan dalam layanan teknologi dan kemudahan teknologi digital menawarkan konsumen berbagai pilihan. Konsumen dengan mudah beralih ke layanan teknologi lain dengan harga yang cukup terjangkau. Penelitian ini juga menemukan bahwa variabel persepsi konsumen terhadap manfaat dan variabel kepercayaan terhadap layanan fintech berpengaruh terhadap sikap konsumen. Namun, kedua variabel tersebut tidak berpengaruh langsung terhadap keinginan untuk terus menggunakan layanan fintech. Variabel persepsi risiko tidak memengaruhi sikap dan keinginan konsumen untuk tetap menggunakan layanan fintech. Variabel sikap memengaruhi keinginan untuk terus menggunakan layanan fintech. Hasil studi menunjukkan bahwa penetrasi fintech meningkat dan konsumen terus menggunakan fintech. Persepsi risiko terhadap fintech yang digunakan konsumen perlu ditingkatkan.Kata kunci: fintech, manfaat dan persepsi risiko, Structural Equation Model